A power-intensive piezoelectric energy harvester with efficient load utilization for road energy collection: Design, testing, and application. (1st October 2022) - Cao, Yangsen; Li, Jiarong; Sha, Aimin; Liu, Zhuangzhuang; Zhang, Fan; Li, Xinzhou
Abstract: Piezoelectric energy harvesters (PEHs) convert mechanical energy into electrical energy providing a new method for road infrastructure energy self-consistency. However, the structural design process of the existing PEH is not clear, some PEH structures have deficiencies, and the secondary construction when PEH is combined with pavements is cumbersome. Given this, considering engineering applications and energy output, the design of a new PEH is expounded from five perspectives. A harvester package structure that utilizes 100% of the vehicle load is proposed. The output characteristics of the PEH are tested, and the effects of the load characteristics and arrangement of the piezoelectric ceramic array inside the harvester on the piezoelectric output are studied. By abandoning the conventional "cold combination" method, the piezoelectric pavement is formed by the "hot combination" method. The feasibility of integral molding PEHs and pavement structures is explored. The piezoelectric response and long-term service performance of the harvester under indirect stress in a pavement structure are tested using accelerated-loading tests. The PEH test results show that the load level and speed significantly affect the piezoelectric output of the harvester. Irrespective of the connection state between piezoelectric ceramics, the array arrangement affects the piezoelectric output. The negative effect of the tandem is more obvious. The power density of the PEH under an excitation of 0.7 MPa–20 Hz reaches 0.0926 mW/cm 3, which is 23.96–138.05% higher than that of the same type of excellent PEH. The piezoelectric pavement loading results show that the piezoelectric response of the harvester indirectly stressed on the pavement depends on the tire load. It is worth noting that vehicle speed can increase the output power of the harvester but not necessarily its energy output. After 500, 000 cycles of loading, the open-circuit voltage of the harvester is reduced by only 2.6%, and the rut depth of the pavement structure is 2.1 mm. The harvesters in piezoelectric pavements are in normal service, and the integrated molding method is a convenient construction method. Finally, the potential normalization factors affecting the energy output of the harvester are discussed, and a method to improve the performance of the piezoelectric pavement composite structure is presented. This study provides a reference for the structural design of PEHs and their road applications. Highlights: The design idea of PEHs was expounded from the perspective of road application. A novel power-intensive energy harvester with efficient load utilization was designed. The energy density of the new PEH was 23.96–138.05% higher than that of others. The feasibility of hot combination method for the application of PEHs was verified.